Toward building a better scaffold: how types of mentor support inform mentor-mentee match relationship quality - Feng, Bo; Nakkula, Michael J.; Jiang, Fei (Frontiers in Psychology, 2024)
In the field of youth mentoring, mentor support, as an important scaffold for youth development, is linked to match relationship quality between mentors and mentees. This study examined associations between the support provided by different categories of mentors and internal match quality among 240 mentors in youth mentoring programs. Four clusters of mentors emerged, representing different combinations of purposes on mentor-mentee interactions. Mentors who focus less on the character development of their mentees would hinder their efforts in other forms of interactions, such as fun, sharing, future outlook, or academics in promoting high overall mentor-mentee internal match quality, including relational quality and instrumental quality. While mentors with less focus on future outlook in their mentoring interactions would result in dysfunction for other purposes in promoting internal instrumental quality. These findings are not influenced by mentors' demographic differences such as gender, age, race, and educational background. The significance of the findings for future research and practice is discussed.